2020
DOI: 10.1111/jan.14662
|View full text |Cite
|
Sign up to set email alerts
|

The development of a behaviour questionnaire for stoma self‐management for persons with bladder cancer and an ileal conduit

Abstract: Aims: To develop and preliminarily test the reliability and validity of a behaviour questionnaire for stoma self-management for patients with bladder cancer after radical cystectomy and ileal conduit. Design: A psychometric instrument validation study conducted in two phases. Methods: The initial version of behaviour questionnaire was developed based on guidelines for people living with a stoma. Five experts validated the content of the preliminary 29-item questionnaire. A cross-sectional survey was then condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Items were analysed using the five indicators of critical ratio, item‐total correlation, corrected item‐total correlation, Cronbach's alpha of deleted item, and communality and factor loadings (Iverach et al, 2016). The acceptable criteria for retaining items were as follows: items with a critical ratio >3.00 (Hsu et al, 2017), item‐total correlations that exceeded 0.40 (Hao et al, 2004), corrected item‐total correlations >.40 (Lau et al, 2016), item deletion decreases in Cronbach's alpha, communalities >.20, and factor loadings >.40 (Rattray & Jones, 2007; Wang et al, 2021). Two items (‘heart rate’ and ‘pain’) failed to meet any of the five indicators in this step and were removed after the discussion of experts involved in Phase 1.…”
Section: Methodsmentioning
confidence: 99%
“…Items were analysed using the five indicators of critical ratio, item‐total correlation, corrected item‐total correlation, Cronbach's alpha of deleted item, and communality and factor loadings (Iverach et al, 2016). The acceptable criteria for retaining items were as follows: items with a critical ratio >3.00 (Hsu et al, 2017), item‐total correlations that exceeded 0.40 (Hao et al, 2004), corrected item‐total correlations >.40 (Lau et al, 2016), item deletion decreases in Cronbach's alpha, communalities >.20, and factor loadings >.40 (Rattray & Jones, 2007; Wang et al, 2021). Two items (‘heart rate’ and ‘pain’) failed to meet any of the five indicators in this step and were removed after the discussion of experts involved in Phase 1.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with advanced disease often require Radical Cystectomy (RC) and Urinary Diversion (UD) 8 , which include Orthotopic Bladder Substitution (OBS), Ileal Conduit (IC), and Cutaneous Ureterostomy (CU) 9 . After undergoing IC or CU, patients need to wear urinary bags for life, which has a significant impact on their quality of life 10,11 .Existing studies have already shown that the quality of life of bladder cancer patients with abdominal wall stomas declines in multiple aspects such as physiology, psychology, role, and social function [12][13][14] . The alteration of physiological urinary pathway due to surgery and the issues that may arise from long-term wearing of urinary…”
mentioning
confidence: 99%
“…Existing studies have already shown that the quality of life of bladder cancer patients with abdominal wall stomas declines in multiple aspects such as physiology, psychology, role, and social function [12][13][14] . The alteration of physiological urinary pathway due to surgery and the issues that may arise from long-term wearing of urinary…”
mentioning
confidence: 99%